PENERAPAN BALOK TIDUR DALAM STRUKTUR BANGUNAN 2 LANTAI - Hafudiansyah, Edward; Mussyafa, Faris; Setiawan, Felix; Amperawan Schipper, Lucky; Dwi Hasyti, Yukeu (Departement of Civil Engineering, Universitas Winaya Mukti, 2024)
Gedung Sate is one of the historic buildings that has become an icon in the city of Bandung, has a long history with a distinctive architectural design. Adjustments: The development of a new building that is adapted to the structural conditions of the existing building has experienced several obstacles, one of which is the free space between the basement floor and the beams in one of the building structures in the Gedung Sate area, namely the Setda Building A. This has resulted in the need for more space. So it is planned to use sleeping beam. This research aims to determine whether the planned sleeping beam dimensions still meet the criteria for calculating reinforcement requirements. The research method used is a qualitative research method with a case study type. Structural calculations were carried out with the help of ETABS software based on SNI 2847 2019. Based on the calculation results, the dimensions required for beam planning are B1 700/500 and B2 are 800/550. With the number of B1 reinforcements being 9D19 at the top support and 5D19 at the bottom support and 7D19 at the top field and 11D19 at the bottom field. Meanwhile, reinforcement for B2 is 8D19 at the top support and 6D19 at the bottom support and 6D19 at the top field and 6D19 at the bottom field.